Mindfulness (MBI) in continuous training and evaluation of the transfer in the public sector - Molina-García, Laura; Bernal-Bravo, César; Martín-Padilla, Antonio Hilario (IJERI: International Journal of Educational Research and Innovation, 2023)
This research article presents the results of transfer to the workplace of the training received by workers of the Diputación de Sevilla. The training action is received as continuous training within the continuous training plans of the Diputación de Sevilla. Specifically, the face-to-face training action is a Mindfulness-Based Intervention (MBI): Mindfulness: cultivating full attention, with a duration of 28 hours. Several parameters of this MBI intervention have been analyzed, one of them the transfer of the knowledge acquired to professional and personal practice. The analyzed data show positive results in all the participants, so it can be affirmed that mindfulness training supposes an improvement in capacities such as patience, resilience, communication, problem solving, stress reduction, among other issues to be highlighted in the business climate and the mental health of the people who make it up.